2013
DOI: 10.1007/s13187-013-0593-7
|View full text |Cite
|
Sign up to set email alerts
|

Un Abrazo Para La Familia: An Evidenced-Based Rehabilitation Approach in Providing Cancer Education to Low-SES Hispanic Co-Survivors

Abstract: We discuss Un Abrazo Para La Familia as an effective, rehabilitation-informed evidence-based model of education, information-sharing, and skill-teaching for use with low-income Hispanic co-survivors of cancer. Over two years, 120 co-survivors participated in the intervention. The majority of participants (96%) were women and all but one reported being Hispanic. Both in Years 1 and 2, we followed the same pre- and post-intervention evaluation design. Based on pre- and post-intervention assessments of cancer-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 19 publications
2
21
0
Order By: Relevance
“…Our findings regarding the importance of incorporating family and cultural values, and accommodating literacy level are consistent with commonly used strategies for adapting content, or modifying deep‐structure components of health interventions . Similarly, interventions for Latino/a survivors have involved co‐survivors, family members, and caregivers, while others have focused on individual survivors …”
Section: Discussionsupporting
confidence: 83%
“…Our findings regarding the importance of incorporating family and cultural values, and accommodating literacy level are consistent with commonly used strategies for adapting content, or modifying deep‐structure components of health interventions . Similarly, interventions for Latino/a survivors have involved co‐survivors, family members, and caregivers, while others have focused on individual survivors …”
Section: Discussionsupporting
confidence: 83%
“…The level of patient-engagement in the design and implementation of the interventions varied, with some studies demonstrating successful methods of engaging Latina survivors [10,13]. Likewise, few studies have examined interventions that involve both Latina survivors and their caregivers [27,30]. One survivor-caregiver intervention led to improvements in QOL for Mexican-American survivors and caregivers [27].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding Q2, based on the item‐level analysis of CKQ items, we found that both samples (Arizona and Portland) did not report statistically significant gains from pre to post on the item about nausea. Second, we did not see pregains to postgains for the item about early detection; this question was specific to the Portland sample only.…”
Section: Resultsmentioning
confidence: 90%
“…Year 2 served as a pilot test of Abrazo's reproducibility, demonstrating it as an effective program that can be disseminated independent of the developer. In both years, results indicated statistically significant improvements for Abrazo participants in cancer knowledge and self‐efficacy . This successful use of trained promotoras provided the basis for the dissemination initiative in Portland, Oregon.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation